Life Expectancy and Health Care Expenditures in the 21st Century: A New Calculation for Germany Using the Costs of Dying - Friedrich Breyer; Stefan Felder (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
Some people believe that the impact of population ageing on future health care ex-penditures will be quite moderate due to the high costs of dying. If not age per se but proximity to death determines the bulk of expenditures, a shift in the mortality risk to higher ages will not affect lifetime health care expenditures as death occurs only once in every life. We attempt to take this effect into account when we calculate the demographic impact on health care expenditures in Germany. From a Swiss data set we derive age-expenditure profiles for both genders, separately for persons in their last four years of life and for survivors, which we apply to the projections of the age structure and mortality rates for the German population between 2002 and 2050 as published by the Statistische Bundesamt. We calculate that at constant prices per-capita health expenditures of Social Health Insurance would rise from – 2,596 in 2002 to between – 2,959 and – 3,102 in 2050 when only the age structure of the population changes and everything else remains constant at the present level, and to – 5,485 with a technology-driven exogenous cost increase of one per cent per annum. A ?na?ve? projection based only on the age distribution of health care expenditures, but not distinguishing between survivors and decedents, yields values of – 3,217 and – 5,688 for 2050, respectively. Thus, the er-ror of excluding the ?costs of dying? effect is small compared with the error of under-estimating the financial consequences of expanding medical technology.
Keywords: 330